Cellular Changes and Apoptosis in the Spleens and Peripheral Blood of Mice Infected with Blood-Stage Plasmodium chabaudi chabaudi AS - Helmby, Helena (American Society for Microbiology, 2000)
Infection with blood-stage Plasmodium chabaudi chabaudi AS results in splenomegaly, peripheral leukocytosis, and a major activation of the immune system. The frequencies and absolute numbers of T-cell, B-cell, and macrophage populations in spleen and peripheral blood from P. chabaudi-infected BALB/c mice were compared and found to be significantly altered during acute infection. The kinetics of the redistribution of the different cell types in spleen and peripheral blood were different, with T and B cells appearing in the blood when their frequencies and absolute numbers in the spleen were low. The frequency and absolute number of apoptotic cells in the spleen were increased during acute P. chabaudi infection and involved both T cells, B cells, and macrophages. Both Fas and Fas-ligand expression were increased in the spleen. Taken together, our data provide new information on the complex cellular interactions that take place in the immune system during blood-stage malaria infection in a mouse model.